Models of youth entrepreneurship encouraging in Kazakhstan: current state, systemic issues and long-term outlook - Khussainova, Zh.S.; Zhartai, Zh.M.; Abauova, G.M.; Lambekova, A.N.; Syzdykova, D.I. (BUKETOV BUSINESS REVIEW, 2020)
Object: The paper seeks to assess the current state of development and effectiveness of support for youth entrepreneurship in Kazakhstan with the development of a long-term strategy for its growth. Methods: We used statistical data analysis, methods of system, structural and functional analysis, as well as SWOT analysis of youth entrepreneurship and its support mechanism in Kazakhstan. Results: We have identified key components of the current model of institutional support for the development of youth entrepreneurship in Kazakhstan and the main parameters of their functional effectiveness. The analysis hasrevealed the following: lack of systematic (integrated) support for the development and encouraging youth entrepreneurship including a program-oriented approach (in particular, a special state program for the development of youth entrepreneurship); availability of a small range of institutional tools for specialized support for the development of youth entrepreneurship (including the lack of a special Fund to support youth entrepreneurship); lack of effective coordinated interdepartmental interaction between state, public and non-state institutional segments to support and encourage youth entrepreneurship. We have revealed main elements of the current model of financial support for youth entrepreneurship in Kazakhstan and its effectiveness’parameters. The analysis has shown the lackof special financial instruments for comprehensive support of youth entrepreneurship and specialized targeted financing of this business segment. We have revealed systemic issues of development of youth entrepreneurship and its support mechanism in Kazakhstan. The result of the study is a detailed SWOT matrix of youth entrepreneurship and its support mechanism in Kazakhstan and extrapolation of its results to promising strategies for further development of the youth segment in the business sector. Conclusions: The effective development of youth entrepreneurship in the country is determined by institutional and economic parameters of the current system and its potential dynamics. It is the opportunities for dynamic promotion that are dominating in the cyclical and possibly circular growth of youth entrepreneurship. This requires application of a new methodology for long-term analysis. One of the most important methods of this approach is the foresight, which we study in the next section of this paper.